ISSUE OF HOLOCAUST TEACHING AT PRIMARY AND SECONDARY SCHOOLS IN SLOVAKIA - HOPTOVÁ, LUCIÁNA (Journal of Education Culture and Society, 2020)
Aim. The primary aim of the study is to examine how the issue of Holocaust is integrated into teaching of history at primary schools and grammar schools in the Slovak Republic. The secondary aim is to present the methodological ideas, suggestions and recommendations for teaching Holocaust in Slovak schools.Methods. The subject of the study is analysis of basic state educational documents defining the compulsory content of education and training for the school subject of history at primary school and grammar school, thus the National Educational Programme for lower secondary education (second stage of primary school) and the National Educational Programme for grammar schools (completed secondary general education), with emphasis to Holocaust. The method of analysis is applied to textbooks of history that contain information of Holocaust. The study also includes a detailed analysis of methodological recommendations and suggestions prepared by the Ministry of Education, Science, Research and Sport of the Slovak Republic and the National Institute for Education to assist teachers in teaching Holocaust issue. The study is supplemented by knowledge from educational practice what was obtained through interview method with 15 teachers of history.Results. Holocaust is an integral part of teaching history at primary schools and grammar schools. Students get acquainted with Holocaust issue in Slovak and global historical context in the 9th year of primary school and in the 3rd year of grammar school with a four-year educational programme. The basic content of education is defined in the eduational standards of national educational programmes. Teachers can specify and concentize it even more within teaching of history. Its development is aided not only by textbooks of history but also by various educational and professional activities defined in various methodological materials and manuals.